PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPSq) DISERTAI DENGAN LEMBARAN KERJA KARTUN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 34 PADANG TAHUN PELAJARAN 2012/2013 - mita, Vebri; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
Background of research by concept comprehension mathematik of student wich still low, the lack of students interest toward mathematik, the sudent is not used to think, the lack of students bravery to ask question to the teacher. The purpose of this research to know how long concept comprehension mathematic of the student which apply Cooperatif Learning Model Think Pair Square (TPSq) Type follow by Cartoon Work sheet as good as comprehension mathematik of the student which learning conventional student class VIII SMPN 34 Padang 2012/2013 academic year. Population is the student grade-VIII of SMPN 34 padang. This research is experimental research, the design of randomized trial on the subject. The instrument used is the final essay test. The technique analysis data that used is the t test one hand. Hypotesis is test result obtained is that tvalue = 2,80 is greather than ttable = 1,645. So hypotesis research resived until we can conclude that concept comprehension mathematic of the student apply cooperatif learning model Think Pair Square (TPSq) type follow by cartoon Work Sheet ask good as consept comprehension mathematic student which apply conventional learning.